ChemInform Abstract: A New Catalyst for the Asymmetric Henry Reaction: Synthesis of β‐Nitroethanols in High Enantiomeric Excess. Issue 19 (18th April 2013) - White, James D.; Shaw, Subrata
Abstract The catalyst system including ligand (I) is successfully applied to the reaction of a broad spectrum of aldehydes with nitromethane and can be extended to a diastereoselective preparation of analogues (XIII) in the presence of nitropropane.